Different diagnostic groups and labour market marginalization among refugee youths. (30th September 2020) - Chen, J; Mittendorfer-Rutz, E; Klimek, P
Abstract: Background: Refugees are at increased risk of labor market marginalization (LMM), which is of high Public Health importance. However, little is known whether specific multimorbidity patterns increase the risk of LMM in this group. We sought to examine whether different diagnostic groups associate with subsequent unemployment and disability pension in refugee youth as compared to their counterparts born in Sweden. Methodology: We analyzed 249, 245 individuals between the age of 16 and 26 at 31.12.2011 from a combined Swedish registry. Refugees were matched to five second-generation-native-born Swedes. LMM was defined as disability pension or > 180 days of unemployment, 2012-2015. Relative risks (RR) were calculated for 114 diagnostic groups (2009-11) with regard to the two outcome measures. Results: The mean age was 23±1.7 years, 2, 841 (1.1%) received disability pension and 16, 323 (6.5%) individuals experienced unemployment. The majority of diagnostic groups was associated with a higher risk for unemployment and a lower risk for disability pension in refugees. Hypertensive diseases and external causes of morbidity showed higher risk ratios of unemployment for refugees compared to Swedish-born: RRs (95% Confidence Interval) 6.8 (3.16, 14.6) and 6.31 (4.45, 8.94), respectively. Diabetes and mental disorders were associated with higher risk estimates for disability pension in refugees: RRs (95% CI) 2.4 (1.02, 5.6) and 1.8 (0.80, 3.9), respectively. Conclusions: Diagnoses are differentially associated with LMM in refugee youth as compared to Swedish-born individuals. In order to prevent LMM in refugees, early intervention for the identified diseases is important. Key message: The importance of diagnostic groups for subsequent LMM differs for young refugees and Swedish-born individuals. Findings are also divergent regarding the measure of LMM.